2002
DOI: 10.1063/1.1494866
|View full text |Cite
|
Sign up to set email alerts
|

Tensile elongation (110%) observed in ultrafine-grained Zn at room temperature

Abstract: Tensile tests were performed for Zn at room temperature, which show elongations of 110%–20% for average grain sizes of 240–23 nm, respectively. The ductility of ultrafine-grained and nanocrystalline Zn was found to decrease with grain size refinement. The deformation mechanisms in ultrafine-grained Zn are believed to be a mixture of grain boundary sliding of small nanograins and intra-grain dislocation creep within the large grains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…64 This type of plastic mechanism cannot be completely excluded in nc metals as nanovoids could become dislocation nucleation or sink sources. Due to the inadequate experimental data on hcp nc metals, [65][66][67] the general trend of m in this class of materials remains unsolved.…”
Section: (4)mentioning
confidence: 99%
“…64 This type of plastic mechanism cannot be completely excluded in nc metals as nanovoids could become dislocation nucleation or sink sources. Due to the inadequate experimental data on hcp nc metals, [65][66][67] the general trend of m in this class of materials remains unsolved.…”
Section: (4)mentioning
confidence: 99%
“…There are two contributions to the plastic work done on the cylinder: that associated with extending the cylinder and that caused by shrinkage relative to the rest of the fiber [1] where s is the shear flow strength of the fiber. Substituting for ␦v(r) and replacing s with y /2, integration then gives [2] For the case of limited decohesion at interfaces with a length of l d (similar to the case of delamination and necking in experiments), the initial crack opening u 0 has to be replaced by the effective decohesion length (l d ϩ u 0 ). In addition, y increases with strain in the ductile metal cylinder ( y ϭ 0 ( y / o ) n , where n is the work-hardening exponent, o is the yield strain, and 0 is the initial flow stress at yield strain), and the strain in the cylinder can be approximated by (u/u 0 Ϫ 1).…”
Section: Enhanced Tensile Ductilitymentioning
confidence: 99%
“…However, low ductility, and the associated loss of toughness, is a serious deficiency in most of these metals. [1] High ductility in nanostructured materials has been observed in a few cases, but these cases appear to be exceptional, [2,3] often occurring only at high temperatures [4] or with microtensile samples using specialized testing equipment. [5] Inspection of the relevant literature reveals that several approaches have been proposed to enhance the ductility of nanostructured materials.…”
Section: Introductionmentioning
confidence: 99%
“…In other words, although each partial produces a strain of magnitude a / 6 , the sum of the total strains produced by the three partials is approximately zero if the numbers of three partials are about the same. It is possible to randomly emit the three Shockley partials, b 1 , b 2 and b 3 , on successive (111) slip planes, which will produce a deformation twin with zero net macrostrain. It has been observed that in nc nickel, a majority of twins are formed by the RAP mechanism.…”
Section: Random Activation Of Partials From Gbmentioning
confidence: 99%
“…1 Nanocrystalline and nanostructured (with structural features less than 100 nm) materials have been reported to have superior mechanical properties such as high strength, which could coexist with very good ductility. [2][3][4] These superior mechanical properties are attributed to their unique deformation mechanisms, which are fundamentally different from those in their coarse-grained (CG) counterparts. [5][6][7][8][9] Particularly, deformation twins have been used to increase the ductility of nanostructured metals.…”
Section: Introductionmentioning
confidence: 99%